AL-HÂJAT AL-AŞLIYYAH DAN HARTA TERBEBAS HUTANG SEBAGAI SYARAT WAJIB ZAKAT MÂL - Mustafa MH. (IAIN BONE, 2021)
AbstractThis article discusses the problem of al-hâjat al-aşliyyah and debt-free assets as a condition of compulsory zakat, which was put forward by scholars in the Mazhab Hanafiyyah. The goal is to avoid mistakes in imposing material religious obligations, such as zakat. Because the obligation of zakat should not be imposed on the poor. The results of the discussion are: First, the Mazhab Hanafiyyah explains the purpose of al-hâjat al-aşliyyah (excess basic needs), namely the fulfillment of survival needs (primary needs) and not secondary needs. Lastly, debt dependents that can cancel zakat obligations, namely debts that reduce the amount of niṣab, and debts related to basic needs and are due for payment.AbstrakArtikel ini membahas masalah al-hâjat al-aşliyyah dan harta bebas utang sebagai syarat wajib zakat, yang dikemukakan oleh para ulama di mazhab Hanafiyyah. Tujuannya agar tidak terjadi kesalahan pembebanan kewajiban-kewajiban agama yang bersifat kebendaan, seperti zakat. Karena kewajiban zakat tidak boleh dibebankan kepada fakir miskin. Hasil pembahasan yaitu: Pertama, Mazhab Hanafiyyah menjelaskan tujuan al-hâjat al-aşliyyah (kelebihan kebutuhan dasar), yaitu pemenuhan kebutuhan kelangsungan hidup (kebutuhan primer) dan bukan kebutuhan sekunder. Terakhir, tanggungan utang yang dapat membatalkan kewajiban zakat, yaitu utang yang mengurangi jumlah niṣab, dan utang yang berkaitan dengan kebutuhan pokok dan sudah jatuh tempo pembayarannya.